Lupeol, a Dietary Triterpene, Enhances Wound Healing in Streptozotocin-Induced Hyperglycemic Rats with Modulatory Effects on Inflammation, Oxidative Stress, and Angiogenesis - Beserra, Fernando Pereira [UNESP]; Vieira, Ana Júlia [UNESP]; Gushiken, Lucas Fernando Sérgio [UNESP]; de Souza, Eduardo Oliveira [UNESP]; Hussni, Maria Fernanda [UNESP]; Hussni, Carlos Alberto [UNESP]; Nóbrega, Rafael Henrique [UNESP]; Martinez, Emanuel Ricardo Monteiro [UNESP]; Jackson, Christopher John; de Azevedo Maia, Gabriela Lemos; Rozza, Ariane Leite [UNESP]; Pellizzon, Cláudia Helena [UNESP] (My University, 2019)
Impaired wound healing is a debilitating complication of diabetes that leads to significant morbidity, particularly foot ulcers. Natural products have shown to be effective in treating skin wounds. Lupeol is known to stimulate angiogenesis, fibroblast proliferation, and expressions of cytokines and growth factors involved in wound healing. The study is performed to evaluate the wound healing activity of lupeol in streptozotocin-induced hyperglycemic rats by macroscopical, histological, immunohistochemical, immunoenzymatic, and molecular methods. Percentage of wound closure and contraction was increased in the lupeol-treated group when compared to the Lanette group. Histopathological observation revealed decreased inflammatory cell infiltration and increased proliferation of fibroblasts, vascularization, and deposition of collagen fibers after lupeol treatment. Immunohistochemical analyses showed decreased intensity of NF-κB and increased intensity of FGF-2, TGF-β1, and collagen III. ELISA results revealed downregulated IL-6 levels and upregulated IL-10 levels in response to lupeol. The mRNA expression levels of Hif-1α, Sod-2, and Ho-1 were significantly increased in response to lupeol as compared to Lanette whereas Nf-κb and Vegf-A levels were decreased in relation to insulin and lupeol treatment. These findings indicate that lupeol possesses wound healing potential in hyperglycemic conditions and may be useful as a treatment for chronic wounds in diabetic patients.